Analysis of Islamic Service Quality and Price on Customer Satisfaction and Repurchase Intention in Umrah Pilgrims in Pekanbaru - Akmalulhadi Akmalulhadi; Zulkarnain Zulkarnain; Lailan Tawila Berampu (Indonesian Journal of Economics, Social, and Humanities, 2026)
The increase in number of Umrah pilgrims and official Umrah provider in Pekanbaru has developed significantly in the period 2019 to 2023. However, complaints related to the organization still exist, such as failure to depart, neglect of pilgrims, services that are not in accordance with minimum standards, and other common problems. This is certainly a challenge and opportunity for Umrah provider to be able to provide the best service for this business to survive and continue to grow. The purpose of this study was to analyze the effect of Islamic service quality and price on customer satisfaction and repurchase intention (willingness to travel again with the same travel). The method used was quantitative description with non-probability sampling technique and a sample size of 175 respondents. Respondents of this study were Umrah pilgrims who came from the city of Pekanbaru. The results of research through SEM show that Islamic service quality has a significant effect on price. Islamic service quality and price have a significant effect on customer satisfaction. Likewise, customer satisfaction affects repurchase intention. Meanwhile, Islamic service quality and price have no significant effect on repurchase intention. Meanwhile, customer satisfaction mediates the effect of Islamic service quality and price on repurchase intention.